An introduction to language - Fromkin, Victoria; Hyams, Nina M. , 1952-; Rodman, Robert (Wadsworth , Cengage Learning, 2011)
The authors' up-to-date descriptions of the major components of language -- phonetics, phonology, morphology,syntax, semantics, and pragmatics -- are presented at an introductory level that assumes no prior knowledge of linguistics. Discussions about the grammar and other linguistic characteristics of American Sign Language, and other sign languages of deaf people, are woven throughout to reveal the pervasive parallels with spoken languages. Each chapter ends with an array of review materials. Numerous exercises offer instructional options and learning opportunities designed to maximize students' comprehension and mastery of text material. --from publisher description